The AI Scribe: Transforming Medical Documentation from Burden to Breakthrough - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The AI Scribe: Transforming Medical Documentation from Burden to Breakthrough The integration of Artificial Intelligence (AI) into healthcare is rapidly...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care